PENYELIDIKAN VALIDITAS ULTRASONIC PULSE VELOCITY DALAM MENCITRAKAN KERETAKAN MIRING PADA BETON NORMAL DENGAN VARIASI SUDUT KEMIRINGAN RETAK - NUGROHO, CANDRA ADI; Wijatmiko, Indradi; Wijaya, Ming Narto (Jurnal Mahasiswa Jurusan Teknik Sipil, 2021)
The need to know the quality of the concrete by way of Non-destructive Test in order to avoid the risk ofstructural failure, one of which is using Ultrasonic Pulse Velocity (UPV). UPV is a set of tools that canidentify the quality of concrete by using ultrasonic wave propagation. The presence of different materials anddiscontinuities such as cracks can be evaluated by the wave propagation. In this research, UPV was used todetermine the effect of inclination cracks in concrete on UPV testing. With unreinforced beam specimensgiven artificial cracks with variations in angles of 90o, 60o, and 45o. The UPV used is PUNDIT PL-200 byutilizing the crack depth method feature. The results obtained in this research are the influence of the angleof the crack on the UPV test results.Keyword : Crack Depth Testing, Inclination Crack in Concrete, Ultrasonic Pulse Velocity,